A Study of Teachings on Dhammakaya in Line with Wat Phra Dhammakaya - Sirivijayo, Phramaha Pongsiri; Kerdchor, Chamnarn (Mahachula Academic Journal, 2024)
The purpose of this article was 1) to study the historical background of the concept of Dhammakaya in Buddhism, 2) to study the teachings of Dhammakaya according to the Dhammakaya Temple’s perspective, and 3) to analyze and comparation of the Dhamma-kaya teachings from the Dhammakaya Temple with the concept of Dhammakaya in other scriptures. This research is a documentary study, and the data was analyzed using content analysis methods. The findings indicate that the concept of Dhammakaya is present in both the Tipitaka and other secondary scriptures. Dhammakaya is used as a name for the Buddha, representing the essence of Dharma or the qualities of enlightenment. In Mahayana Buddhism, Dhammakaya is one of the three bodies (Trikaya) used to explain the different states of the Buddha. In contrast, the Dhammakaya Temple regards Dhammakaya as the most refined body of a human being, composed of the highest purity. The meditation practice at the Dhammakaya Temple is distinctive, involving the visualization of a bright crystal ball at the center of the body. In later teachings, practitioners are also instructed to keep the mind empty to achieve deep meditation. The comparison of the Dhammakaya teachings with other scriptural interpretations reveals that the term "Dhammakaya" appears four times in the Tipitaka. Generally, Theravada scholars agree that the Buddha has two bodies: the physical body (Rupakaya) and the Dhammakaya. In Mahayana Buddhism, Dhammakaya is a specific name used for the Buddha, associated with concepts like Tathagata and Nibbana.